Non-invasive estimation of split renal function from routine 68Ga-SSR-PET/CT scans - Weissinger, Matthias; Seyfried, Kyra Celine; Ursprung, Stephan; Castaneda-Vega, Salvador; Seith, Ferdinand; von Beschwitz, Sebastian; Vogel, Jonas; Ghibes, Patrick; Nikolaou, Konstantin; la Fougère, Christian; Dittmann, Helmut (Frontiers in Medicine, 2023)
Objective Patients with impaired kidney function are at elevated risk for nephrotoxicity and hematotoxicity from peptide receptor radionuclide therapy (PPRT) for advanced neuroendocrine tumors. Somatostatin receptor (SSR)-PET/CT imaging is the method of choice to identify sufficient SSR expression as a prerequisite for PRRT. Therefore, our study aimed to explore whether split renal function could be evaluated using imaging data from routine SSR-PET/CT prior to PRRT. Methods In total, 25 consecutive patients who underwent SSR-PET/CT (Siemens Biograph mCT®) before PRRT between June 2019 and December 2020 were enrolled in this retrospective study. PET acquisition in the caudocranial direction started at 20 ± 0.5 min after an i.v. injection of 173 ± 20 MBq [68Ga]Ga-ha DOTATATE, and the kidneys were scanned at 32 ± 0.5 min p.i. The renal parenchyma was segmented semi-automatically using an SUV-based isocontour (SUV between 5 and 15). Multiple parameters including SUVmean of renal parenchyma and blood pool, as well as parenchyma volume, were extracted, and accumulation index (ACI: renal parenchyma volume/SUVmean) and total kidney accumulation (TKA: SUVmean x renal parenchyma volume) were calculated. All data were correlated with the reference standard tubular extraction rate (TER-MAG) from [99mTc]Tc-MAG3 scintigraphy and glomerular filtration rate (GFRCDK − EPI). Results SUVmean of the parenchymal tracer retention showed a negative correlation with TERMAG (r: −0.519, p < 0.001) and GFRCDK − EPI (r: −0.555, p < 0.001) at 32 min p.i. The herein-introduced ACI revealed a significant correlation (p < 0.05) with the total tubular function (r: 0.482), glomerular renal function (r: 0.461), split renal function (r: 0.916), and absolute single-sided renal function (r: 0.549). The mean difference between the split renal function determined by renal scintigraphy and ACI was 1.8 ± 4.2 % points. Conclusion This pilot study indicates that static [68Ga]Ga-ha DOTATATE PET-scans at 32 min p.i. may be used to estimate both split renal function and absolute renal function using the herein proposed “Accumulation Index” (ACI).